The Impact COVID-19 Pandemic on Productivity of Tax Return Document Processing in the New Normal Era at Tax Data and Document Processing Center - Pri Budiarti Rini Sejati (Program Pascasarjana Universitas Negeri Makassar, 2020)
This study aims to determine the impact of the Covid-19 Pandemic on the productivity of documents in the New Normal Era at PPDDP. This type of research is a descriptive study, with a research focused by analyzing the production of Tax Return document processing before and after the Covid-19 pandemic. The Purpose of this scientific article is to provide a new view to the State Civil Service (SCS) that the normal era is a pushing factor or triger for future organizational management innovation.The method used in this study is a qualitative approach. Data collection was carried out through direct interviews with employees in the Taxation Data and Document Processing Center. The key informants in this study were employees of the Document Collection and Receiving Section and the Recording and Data Transfer Section. This study shows that there were changes in behavior and habits at work such as lessening work days due to the Work From Office and Work From Home policies leading to a significant decrease in the productivity of Tax Return document processing. The higher number of employees and work days (as well as work hours/day) in office the higher number of processed Tax Return documents. The number of Tax Return documents processing in the new era is normal has significant decreased due to limited human resources available in office and decreasing work days.